REVOLUTIONIZING PEDAGOGY: THE TASK-DRIVEN COLLABORATIVE INQUIRY APPROACH IN MODERN EDUCATIONAL TECHNOLOGY INSTRUCTION - Xinyi , Wang Wei Li (Top Educational Review Journal (TERJ), 2023)
The modern educational technology course, primarily designed for teacher training students, plays a pivotal role in shaping their educational competence and proficiency. A comprehensive understanding and command of modern educational technology profoundly influence their capacity for applying, integrating, and innovating in the context of educational informatization. To optimize the efficacy of modern educational technology instruction, educators must embrace scientific and rational teaching methods, evolve beyond conventional practices, and emphasize task-driven pedagogy. Fostering collaborative inquiry among students serves as a key strategy to facilitate their grasp of contemporary educational theories and models. This approach equips students with a robust foundation of both theoretical knowledge and practical skills, fortifying their readiness for future professional roles. It is imperative for university educators to recognize the paramount value of task-driven and collaborative inquiry methodologies in modern educational technology instruction, coupling them harmoniously with specific course content to elevate the overall quality of pedagogy.